The impact of same‐day and rapid ART initiation under the Universal Health Coverage programme on HIV outcomes in Thailand: a retrospective real‐life cohort study - Sirinya Teeraananchai; David C. Boettiger; Cheewanan Lertpiriyasuwat; Rattaphon Triamwichanon; Patchara Benjarattanaporn; Nittaya Phanuphak (Journal of the International AIDS Society)
Abstract Introduction Antiretroviral therapy (ART) initiation, regardless of CD4 count, has been recommended in Thailand since 2014, with same‐day initiation recommended since 2021. We assessed HIV treatment outcomes among Thai people living with HIV (PLHIV) by the time from HIV diagnosis to ART initiation under the Universal Health Coverage (UHC) programme and identified factors associated with virological failure (VF). Methods PLHIV aged ≥15 years initiating ART between 2014 and 2022 were included from the UHC database. We categorized participants into four groups using the duration from HIV diagnosis to ART initiation: (1) ≤ 7 days (same‐day ART); (2) 8 days to <1 month; (3) 1–3 months; and (4) >3 months. Viral load (VL) was measured 6 months after starting ART, and annually thereafter. VF was defined as VL ≥1000 copies/ml. Factors associated with VF were analysed using competing risk models considering death and loss to follow‐up (LTFU) as competing events. Results Among 252,239 PLHIV who started ART, the median age at initiation was 34 years (interquartile range [IQR]: 26–43 years). The median (IQR) pre‐ART CD4 count was 233 (76–420) cells/mm3. ART initiation occurred within 7 days for 25% (17% on the same day, 8% in 2–7 days), 24% in 8 days to <1 month, 23% in 1–3 months and 28% in >3 months. ART initiation within 7 days increased from 20% (2014–2016) to 32% (2021–2022). VF occurred with a rate of 3.11 (95% CI 3.07–3.159) per 100 person‐years (PYs). PLHIV initiating ART 8 days to 1 month were at lower risk of VF (aSHR 0.52, 95% CI 0.50–0.54) when compared to ART initiation >3 months. ART initiation within 7 days resulted in the lowest mortality (6%: 1.28 [95% CI 1.24–1.32] per 100 PYs), but the highest rate of LTFU (12%: 2.69 [95% CI 2.63–2.75] per 100 PYs) when compared to other ART initiation groups. Conclusions Although ART initiation within 7 days has increased in Thailand, the overall rate of early initiation remains low. ART initiation within 1 month significantly lowered the risk of VF. ART initiation within 7 days significantly reduced mortality. To further optimize health outcomes, innovative strategies are urgently needed to promote earlier ART initiation in Thailand.